ChemInform Abstract: Ferromagnetic α‐Fe2O3NPs: A Potential Catalyst in Sonogashira—Hagihara Cross Coupling and Hetero‐Diels—Alder Reactions. Issue 30 (July 2016) - Kataria, Meenal; Pramanik, Subhamay; Kaur, Navleen; Kumar, Manoj; Bhalla, Vandana
Abstract: Ferromagnetic α‐Fe2 O3 nanoparticles are shown to be an efficient catalyst for Sonogashira—Hagihara cross coupling and hetero Diels—Alder reactions.